Deplating solution and electrolytic deplating method
Through the composite deplating solution of organic salts, chelating agents, pH buffers, wetting agents and deionized water, the problems of deplating solution in the prior art damage to substrates and poor safety and environmental protection, achieving an efficient and safe and safe removal effect of chromium-containing film.
Patent Information
- Application Number
- CN202410314275.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-19
- Publication Date
- 2025-04-18
AI Technical Summary
When the existing deplating solution removes the chromium-containing film layer, it is easy to damage the substrate, and it is poor to materials with poor corrosion resistance, poor safety and environmental protection, and cannot efficiently remove the chromium and chromium-containing film layers on the surface of substrates such as stainless steel and titanium alloys.
The efficient composite deplating solution is adopted with organic salts, chelating agents, pH buffers, wetting agents and deionized water. By regulating the pH and conductivity of the deplating solution, the rate of electrolytic reaction and the uniformity of the deplating are coordinated to achieve efficient removal of the chromium-containing film layer without damaging the metal substrate.
It has achieved efficient removal of the chromium-containing film layer on the surface of the metal substrate, with good deplating effect, safe and environmentally friendly, and does not destroy materials and environments with poor corrosion resistance.
Smart Images

Figure CN119843346A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of deplating, and in particular to a deplating solution and an electrolytic deplating method. Background Art
[0002] In the prior art, there are two methods for stripping chromium-containing films: chemical stripping and electrolytic stripping. The stripping solution used in the chemical stripping method usually contains a strong oxidant, which can easily damage the substrate; when there are multiple materials on the workpiece to be stripped, the material with poor corrosion resistance can be easily corroded.
[0003] Most of the deplating solutions used in the existing electrolytic deplating methods contain inorganic strong acids, nitrates, halogens, surfactants or peroxides, etc. These deplating solutions not only have adverse effects on materials with poor corrosion resistance, but also have poor safety and environmental protection. At present, there is no deplating solution and electrolytic deplating method that can efficiently remove chromium and chromium-containing film layers on the surface of substrates without damaging substrates such as stainless steel, titanium alloy, stainless steel-aluminum alloy laminated materials and titanium alloy-aluminum alloy laminated materials. Summary of the invention
[0004] In view of this, the present application provides a deplating solution and an electrolytic deplating method. The deplating solution adopts an efficient compound of organic salts, chelating agents, pH buffers, wetting agents and deionized water, which can efficiently remove the chromium-containing film layer on the surface of the metal substrate, has good deplating effect, and is safe and environmentally friendly.
[0005] In a first aspect, the present application provides a deplating solution for stripping a chromium-containing film layer. Based on the total mass of the deplating solution, the deplating solution comprises 1-15wt% of an organic salt, 0.1-5wt% of a chelating agent, 1-15wt% of a pH buffer, 0.1-3wt% of a wetting agent and 60-95wt% of deionized water; wherein the organic salt is an organic acid sodium salt and / or an organic acid potassium salt.
[0006] Optionally, the organic acid sodium salt includes one or more of sodium gluconate, sodium aspartate, potassium sodium tartrate, sodium tartrate, sodium citrate, sodium malate, disodium iminosuccinate and tetrasodium iminodisuccinate; The organic acid potassium salt includes one or more of potassium gluconate, potassium tartrate, potassium citrate and potassium malate.
[0007] Optionally, based on the total mass of the deplating solution, the deplating solution consists of 1-15wt% of an organic salt, 0.1-5wt% of a chelating agent, 1-15wt% of a pH buffer, 0.1-3wt% of a wetting agent and 60-95wt% of deionized water.
[0008] Optionally, based on the total mass of the deplating solution, the deplating solution consists of 5-10wt% of an organic salt, 0.1-2wt% of a chelating agent, 3-8wt% of a pH buffer, 0.5-2wt% of a wetting agent and 75-95wt% of deionized water.
[0009] Optionally, the pH of the deplating solution is 4-7.
[0010] Optionally, the pH of the deplating solution is 5.5-6.5.
[0011] Optionally, the conductivity of the deplating solution is 10000-100000 μs / cm.
[0012] Optionally, the chelating agent includes one or more of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, hydroxyethylidene diphosphonic acid, disodium hydroxyethylidene diphosphonic acid and tetrasodium hydroxyethylidene diphosphonic acid.
[0013] Optionally, the pH buffer comprises an organic acid and a phosphate; wherein the organic acid comprises one or more of aminoacetic acid, glycolic acid, citric acid, malic acid and tartaric acid; The phosphate includes one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate and dipotassium hydrogen phosphate.
[0014] Optionally, the mass ratio of the organic acid to the phosphate is 1:(0.5-15).
[0015] Optionally, the mass ratio of the organic acid to the phosphate is 1:(1-10).
[0016] Optionally, the wetting agent is one or more of ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol butyl ether, propylene glycol, glycerol, isopropyl alcohol, polyvinyl pyrrolidone and polyethylene glycol.
[0017] In a second aspect, the present application provides an electrolytic stripping method, comprising the following steps: using a metal substrate having at least a portion of its surface covered with a chromium-containing film layer as an anode and placing it in a stripping solution for electrolytic stripping; the stripping solution is the stripping solution described in the first aspect of the present application.
[0018] Optionally, the temperature of the deplating solution is 10-45°C; the current density of the deplating solution is 0.5-5A / dm 2 ; The electrolytic stripping time is 5-30min.
[0019] Optionally, the temperature of the deplating solution is 20-25°C; the current density of the deplating solution is 1-2.5A / dm 2 .
[0020] Optionally, the chromium-containing film layer includes one or more of a metallic chromium plating layer, a chromium carbide, a chromium nitride and a chromium carbonitride.
[0021] Optionally, the metal substrate includes one of stainless steel, titanium alloy, stainless steel-aluminum alloy laminated material and titanium alloy-aluminum alloy laminated material.
[0022] Optionally, the cathode material comprises one of stainless steel or graphite plate.
[0023] Through the above technical scheme, the deplating solution of the present application is efficiently compounded by organic salt, chelating agent, pH buffer, wetting agent and deionized water, and the organic salt is organic acid sodium salt and / or organic acid potassium salt. The present application uses organic salt and pH buffer to coordinately regulate the pH and conductivity of the deplating solution, thereby regulating the rate of electrolytic reaction and the uniformity of deplating, and improving the efficiency of electrolytic deplating without damaging the metal substrate.
[0024] Other features and advantages of the present application will be described in detail in the subsequent detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is a diagram showing the deplating effect of the stainless steel workpiece after electrolytic deplating in Example 3 of the present application; Figure 2 This is a diagram showing the deplating effect of the aluminum alloy surface of the stainless steel-aluminum alloy laminated material workpiece after electrolytic deplating in Example 6 of the present application; Figure 3 This is a picture showing the deplating effect of a stainless steel workpiece after electrolytic deplating in Comparative Example 1 of the present application; Figure 4 This is a picture showing the deplating effect of the stainless steel surface of the stainless steel-aluminum alloy laminated material workpiece after electrolytic deplating in Comparative Example 2 of the present application; Figure 5 This is a picture showing the effect of stainless steel surface deplating after electrolytic deplating of a stainless steel-aluminum alloy laminated material workpiece in comparative example 4 of the present application; DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0028] The present application provides a deplating solution, which comprises 1-15wt% of an organic salt, 0.1-5wt% of a chelating agent, 1-15wt% of a pH buffer, 0.1-3wt% of a wetting agent and 60-95wt% of deionized water, based on the total mass of the deplating solution. The deplating solution is easily prepared by adopting efficient compounding of organic salt, chelating agent, pH buffer, wetting agent and deionized water, synergistic coordination of multiple components, simple ingredients and easy preparation of the deplating solution.
[0029] In one embodiment of the present application, based on the total mass of the decoating solution, the decoating solution is composed of 1-15wt% of an organic salt, 0.1-5wt% of a chelating agent, 1-15wt% of a pH buffer, 0.1-3wt% of a wetting agent and 60-95wt% of deionized water. In other words, the decoating solution described in the present application is only composed of an organic salt, a chelating agent, a pH buffer, a wetting agent and deionized water, and no other components are present. The decoating solution does not contain components such as inorganic strong acids, inorganic strong bases, halogens, peroxides, persulfates, nitrates, etc., and the above-mentioned components not only have adverse effects on metal substrates with poor corrosion resistance, but also have poor safety and environmental protection. Therefore, the components of the decoating solution are safe and environmentally friendly, and do not damage the environment while being friendly to metal substrates with poor corrosion resistance.
[0030] In one embodiment of the present application, based on the total mass of the decoating solution, the mass content of the organic salt in the decoating solution is 1-15wt%, and can be further preferably 5-10wt%, which is helpful to regulate the conductivity of the decoating solution. Specifically, the mass content of the organic salt in the decoating solution can be, but is not limited to, 1.5%, 3%, 4%, 5%, 6%, 8%, 9%, 10%, 14% or 15%, etc. The organic salt is an organic acid sodium salt and / or an organic acid potassium salt, and the organic acid sodium salt includes one or more of sodium gluconate, sodium aspartate, potassium sodium tartrate, sodium tartrate, sodium citrate, sodium malate, disodium iminosuccinate and tetrasodium iminodisuccinate; the organic acid potassium salt includes one or more of potassium gluconate, potassium tartrate, potassium citrate and potassium malate. Specifically, the organic salt can be sodium gluconate, potassium gluconate, sodium aspartate, potassium sodium tartrate, sodium tartrate, potassium tartrate, sodium citrate, potassium citrate, sodium malate, potassium malate, disodium iminosuccinate, tetrasodium iminodisuccinate, or any combination of the above substances. The organic salt can adjust the conductivity of the deplating solution and control the conductivity within the range of 10000-100000 μs / cm; the higher the conductivity of the deplating solution, the faster the electron transfer, thereby indirectly regulating the electrolytic reaction rate of the chromium-containing coating. In addition, the above-mentioned organic salts are different from strong electrolytes, and there is a certain balance in their ionization, which can make the deplating effect more uniform.
[0031] In one embodiment of the present application, based on the total mass of the deplating solution, the pH value of the deplating solution is The mass content of the buffer is 1-15wt%, and can be further preferably 3-8wt%, which helps to regulate the hydrogen ion concentration in the decoating solution. Specifically, the mass content of the pH buffer in the decoating solution can be, but not limited to, 1.5%, 2.1%, 3%, 6.5%, 7% or 13%, etc.; wherein the mass content of the organic acid in the decoating solution can be, but not limited to, 0.5%, 1%, 1.1%, 1.3%, 1.5% or 2%, etc., and the mass content of the phosphate in the decoating solution can be, but not limited to, 0.8%, 1%, 1.5%, 5%, 6% or 12%, etc. The pH buffer includes organic acids and phosphates; wherein the organic acids include one or more of aminoacetic acid, glycolic acid, citric acid, malic acid and tartaric acid; specifically, the organic acid can be aminoacetic acid, glycolic acid, citric acid, malic acid, tartaric acid, or any combination of the above substances; the phosphate includes one or more of sodium dihydrogen phosphate (NaH2PO4), disodium hydrogen phosphate (Na2HPO4), potassium dihydrogen phosphate (KH2PO4) and dipotassium hydrogen phosphate (K2HPO4); specifically, the phosphate can be NaH2PO4, Na2HPO4, KH2PO4, K2HPO4, or any combination of the above substances. Therefore, the pH buffer can be any combination of the above organic acid and the above phosphate; specifically, the pH buffer can be citric acid and Na2HPO4, malic acid and Na2HPO4, tartaric acid and K2HPO4, citric acid, Na2HPO4 and KH2PO4, malic acid and K2HPO4, or a combination of citric acid, Na2HPO4 and NaH2PO4, etc. The addition of the pH buffer can keep the hydrogen ion content in the water stable, thereby making the stripping effect more stable.
[0032] In this application, when the acid radicals are the same, the solubility of sodium salt and potassium salt in water is higher, and Na + and K + The degree of ionization in liquid is very high, and it has excellent ionic conductivity, which makes the transmission resistance of current in it small. When organic acid sodium salt or organic acid potassium salt ionizes sodium ions or potassium ions, it also ionizes organic acid root ions. Organic acid root ions will undergo a certain degree of hydrolysis in aqueous solution. Its hydrolysis degree will affect the pH value of the solution, and it will also be affected by the original H + The present application utilizes organic salts and pH buffers to coordinately regulate the pH and conductivity of the deplating solution, thereby regulating the rate of the electrolytic reaction and the uniformity of the deplating, thereby improving the efficiency of the electrolytic deplating without damaging the metal substrate.
[0033] In one embodiment of the present application, the mass ratio of the organic acid to the phosphate in the pH buffer is 1:(0.5-15), and can further be preferably 1:(1-10); specifically, the mass ratio of the organic acid to the phosphate can be, but is not limited to, 0.083, 0.4, 0.5, 1, 1.1 or 1.625. The deplating solution mainly removes the chromium-containing film layer on the surface of the metal substrate by the gas generated by electrolyzing water. The content of hydrogen ions in the solution will affect the rate of water electrolysis, thereby affecting the efficiency of deplating; the mass ratio of the organic acid to the phosphate within this range can keep the hydrogen ion content in the water relatively stable, and the deplating effect is better.
[0034] In one embodiment of the present application, based on the total mass of the deplating solution, the mass content of the chelating agent in the deplating solution is 0.1-5wt%, and can be further preferably 0.1-2wt%, which helps to better chelate the chromium ions peeled off from the surface of the substrate. Specifically, the mass content of the chelating agent in the deplating solution can be, but is not limited to, 0.1%, 0.5%, 1% or 3%, etc. The chelating agent includes one or more of ethylenediaminetetraacetic acid (EDTA), disodium ethylenediaminetetraacetate (EDTA-2Na), tetrasodium ethylenediaminetetraacetate (EDTA-4Na), hydroxyethylidene diphosphonic acid (HEDP), disodium hydroxyethylidene diphosphonic acid (HEDP-2Na), and tetrasodium hydroxyethylidene diphosphonic acid (HEDP-4Na); specifically, the chelating agent can be EDTA, EDTA-2Na, EDTA-4Na, HEDP, HEDP-2Na, HEDP-4Na, or any combination of the above substances. The chelating agent has a chelating effect on the chromium ions stripped from the surface of the substrate, thereby preventing the formation of insoluble matter on the surface of the substrate, thereby inhibiting anode polarization.
[0035] In one embodiment of the present application, based on the total mass of the deplating solution, the mass content of the wetting agent in the deplating solution is 0.1-3wt%, and can be further preferably 0.5-2wt%, which helps to reduce the surface tension of water and make the electrolysis reaction more uniform. Specifically, the mass content of the wetting agent in the deplating solution can be, but is not limited to, 0.5%, 1% or 2%, etc. The wetting agent includes one or more of ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol butyl ether, propylene glycol, glycerol, isopropanol, polyvinyl pyrrolidone and polyethylene glycol; specifically, the wetting agent can be ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol butyl ether, propylene glycol, glycerol, isopropanol, polyvinyl pyrrolidone, polyethylene glycol, or any combination of the above substances. The surface tension of the wetting agent is lower than that of water, which can improve the solubilization, penetration and wetting ability of the deplating solution on the surface of the metal substrate, improve the wettability of the surface of the metal substrate, and make the deplating effect better and more uniform.
[0036] In one embodiment of the present application, the pH of the deplating solution is 4-7, and may be further preferably 5.5-6.5; specifically, the pH of the deplating solution may be, but is not limited to, 4.2, 4.5, 5, 5.5, 6.2, 6.6 or 6.8. The pH of the deplating solution has an important influence on the electrolytic stripping process. A suitable pH range can promote the electrolytic stripping and improve the efficiency and quality of the electrolytic stripping. Proper adjustment of the pH value can promote the dissolution of the target metal and inhibit the dissolution of other metals that do not need to be dissolved, which helps to remove a specific coating without affecting the substrate. Too high or too low pH may cause the components in the deplating solution to decompose or precipitate, thereby affecting the effect of the stripping.
[0037] In one embodiment of the present application, the conductivity of the deplating solution is 10000-100000 μs / cm; specifically, the conductivity of the deplating solution may be but is not limited to 15365 μs / cm, 17278 μs / cm, 26101 μs / cm, 46196 μs / cm, 63201 μs / cm, 80836 μs / cm or 40654 μs / cm, etc. The conductivity directly affects the transfer efficiency of the current in the deplating solution and the deplating effect. When the deplating solution has a higher conductivity, the current is transferred more smoothly in the deplating solution, reducing resistance and energy loss, thereby improving the current transfer efficiency, which helps more current to reach the surface of the coating and promotes rapid dissolution; and the improvement of the current transfer efficiency allows more current to reach the surface of the coating, accelerating the generation and removal of metal ions, thereby shortening the deplating time and accelerating the deplating rate; the conductivity of the deplating solution also affects the uniformity of the deplating. If the conductivity is too low, the current may be unevenly distributed on the surface of the coating. Uniform conductivity distribution helps to ensure that the current is evenly transferred on the entire surface of the coating, thereby achieving a uniform deplating effect. Controlling the conductivity of the deplating solution within a preferred range is conducive to further improving the effect of electrolytic deplating.
[0038] The present application provides an electrolytic stripping method, comprising the following steps: using a metal substrate having at least a portion of its surface covered with a chromium-containing film as an anode, and placing the metal substrate together with a cathode material in a stripping solution for electrolytic stripping; the stripping solution is the above-mentioned stripping solution.
[0039] In one embodiment of the present application, the temperature of the deplating solution in the electrolytic deplating method is 10-45°C, and the current density of the deplating solution is 0.5-5A / dm 2 The electrolytic stripping time is 5-30min; further, the temperature of the stripping solution is preferably 20-25°C, and the current density of the stripping solution is preferably 1-2.5A / dm 2Specifically, the temperature of the deplating solution may be, but is not limited to, 20°C, 25°C, or 40°C; the current density of the deplating solution may be, but is not limited to, 0.5A / dm 2 , 1A / dm 2 , 2A / dm 2 or 2.5A / dm 2 etc.; the time of the electrolytic stripping may be, but is not limited to, 5min, 10min or 20min, etc. The temperature and current density of the deplating solution are two key parameters in the electrolytic stripping process. The temperature of the deplating solution can affect the rate and efficiency of the electrolytic stripping. As the temperature increases, the chemical reaction rate in the deplating solution accelerates. Therefore, appropriately increasing the temperature of the deplating solution can shorten the stripping time and improve the stripping efficiency; however, too high a temperature may also cause the deplating solution to be unstable or produce other adverse reactions, so the preferred temperature range can ensure better electrolytic stripping. Secondly, the current density of the deplating solution directly affects the rate and quality of the electrolytic stripping. A higher current density usually leads to a higher electrolytic stripping rate. However, too high a current density may also cause some problems in the stripping process, such as uneven stripping. The regulation of the temperature and current density of the deplating solution is conducive to improving the rate and efficiency of the electrolytic stripping.
[0040] In one embodiment of the present application, the metal substrate in the above-mentioned electrolytic stripping method includes one of stainless steel, titanium alloy, stainless steel-aluminum alloy laminated material and titanium alloy-aluminum alloy laminated material; specifically, the metal substrate can be stainless steel, titanium alloy, stainless steel-aluminum alloy laminated material, or titanium alloy-aluminum alloy laminated material.
[0041] In one embodiment of the present application, the chromium-containing film layer in the electrolytic stripping method comprises a metal chromium plating layer (Cr), a chromium carbide (CrC x ), chromium nitride (CrN x ) and chromium carbonitride (CrC x N y ) one or more; specifically, the chromium-containing film layer may be a Cr film layer, may be a CrC x The coating can be CrN x Film layer, can be CrC x N y The film layer can also be a composite film layer of any combination of the above substances.
[0042] That is to say, the electrolytic stripping method is applicable to Cr, CrC x CrN x and CrC x N yFilm layer; specifically, suitable for at least part of the surface covered with Cr and CrN x The stainless steel of the composite film layer is at least partially covered with CrC x The stainless steel of the film layer is at least partially covered with CrC x The stainless steel-aluminum alloy laminated material of the film layer is at least partially covered with CrC x N y The titanium alloy-aluminum alloy laminated material of the film layer and at least a portion of the surface is covered with CrC x N y The workpieces such as stainless steel-aluminum alloy laminated materials of the film layer. And the above workpieces are used as anode materials in the electrolytic stripping process. The anode is the place where the chromium-containing film layer dissolves, that is, the chromium-containing film layer loses electrons and is oxidized at the anode, and then enters the stripping solution in the form of ions.
[0043] In one embodiment of the present application, the cathode material in the above-mentioned electrolytic stripping method includes one of stainless steel or graphite plate. During the electrolytic stripping process, the cathode is used to receive the metal ions dissolved from the anode and reduce them to metal on the cathode surface; graphite has good electrical conductivity, chemical stability and high corrosion resistance, and is not easy to react with the chemical components in the stripping solution, and is suitable for use as a cathode in the electrolytic stripping process; in some cases, materials such as stainless steel can also be used as the cathode. The selection of the specific cathode material can be based on comprehensive considerations of factors such as its electrical conductivity, chemical stability and corrosion resistance, and this application does not make specific limitations.
[0044] The electrolytic stripping method comprises: placing a metal workpiece having at least a portion of its surface covered with a chromium-containing film as an anode and a stainless steel or graphite plate as a cathode in a stripping solution, wherein the temperature of the stripping solution is 10-45° C. and the current density of the stripping solution is 0.5-5 A / dm 2 The electrolytic stripping time is 5-30min, and the workpiece is removed and cleaned.
[0045] The effect of the technical solution of this application is further illustrated below through specific examples.
[0046] Example 1 The composition of the deplating solution of the present embodiment is as follows: 2wt% potassium sodium tartrate, 1wt% EDTA-2Na, 1.1wt% citric acid, 1.0wt% Na2HPO4, 1wt% polyvinyl pyrrolidone (K30), 93.9wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 4.2 and a conductivity of 15365μs / cm.
[0047] The electrolytic stripping process is as follows: The metal Cr and CrN xThe stainless steel workpiece of the composite film layer is used as the anode and the graphite plate is used as the cathode. The workpiece and the graphite plate are placed in the above-mentioned deplating solution at a current density of 2A / dm 2 , electrolytic stripping is carried out at a temperature of 20° C. for 5 min, and the workpiece is taken out and cleaned.
[0048] Example 2 The composition of the deplating solution of the present embodiment is as follows: 3wt% sodium gluconate, 1wt% tetrasodium iminodisuccinate, 0.5wt% HEDP-2Na, 1.3wt% malic acid, 0.8wt% Na2HPO4, 1wt% diethylene glycol butyl ether, 92.4wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 4.5 and a conductivity of 17278μs / cm.
[0049] The electrolytic stripping process is as follows: The metal Cr and CrN x The stainless steel workpiece of the composite film layer is used as the anode and the graphite plate is used as the cathode. The workpiece and the graphite plate are placed in the above-mentioned deplating solution at a current density of 1A / dm 2 , electrolytic stripping was carried out at a temperature of 25° C. for 10 min, and the workpiece was taken out and cleaned.
[0050] Example 3 The composition of the deplating solution of the present embodiment is as follows: 2wt% sodium aspartate, 2wt% tetrasodium iminodisuccinate, 0.5wt% HEDP-2Na, 1.5wt% tartaric acid, 1.5wt% K2HPO4, 1wt% diethylene glycol butyl ether, 91.5wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 5.0 and a conductivity of 26101μs / cm.
[0051] The electrolytic stripping process is as follows: CrC x The stainless steel workpiece of the film layer is used as the anode, and the stainless steel plate is used as the cathode. The workpiece and the graphite plate are placed in the above deplating solution at a current density of 0.5A / dm 2 , electrolytic stripping is carried out at a temperature of 40° C. for 20 min, and the workpiece is taken out and cleaned.
[0052] Example 4 The composition of the deplating solution of the present embodiment is as follows: 2wt% sodium aspartate, 2wt% sodium gluconate, 0.1wt% EDTA-2Na, 0.5wt% citric acid, 4wt% Na2HPO4, 2wt% KH2PO4, 1wt% polyethylene glycol 200, 88.4wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 6.8 and a conductivity of 46196μs / cm.
[0053] The electrolytic stripping process is as follows: CrC x The stainless steel-aluminum alloy laminated material workpiece (the CrC x The film layer is on the surface of the stainless steel material) as the anode, the graphite plate as the cathode, the workpiece and the graphite plate are placed in the above deplating solution, and the current density is 2.5A / dm 2 , electrolytic stripping was carried out at a temperature of 25°C for 15 minutes, and the workpiece was taken out and cleaned.
[0054] Example 5 The composition of the deplating solution of the present embodiment is as follows: 2wt% sodium aspartate, 2wt% sodium gluconate, 0.1wt% EDTA-2Na, 0.5wt% citric acid, 4wt% Na2HPO4, 2wt% KH2PO4, 1wt% polyethylene glycol 200, 88.4wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 6.8 and a conductivity of 46196μs / cm.
[0055] The electrolytic stripping process is as follows: CrC x Titanium alloy-aluminum alloy laminated material workpiece (the CrC x The film layer is on the surface of the titanium alloy material) as the anode, the graphite plate as the cathode, the workpiece and the graphite plate are placed in the above-mentioned deplating solution, and the current density is 2.5A / dm 2 , electrolytic stripping was carried out at a temperature of 25° C. for 10 min, and the workpiece was taken out and cleaned.
[0056] Example 6 The composition of the deplating solution of the present embodiment is as follows: 8wt% potassium sodium tartrate, 6wt% sodium gluconate, 0.5wt% EDTA-2Na, 2wt% malic acid, 5wt% K2HPO4, 2wt% propylene glycol butyl ether, 76.5wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 6.2 and a conductivity of 63201μs / cm.
[0057] The electrolytic stripping process is as follows: CrC x N yThe stainless steel-aluminum alloy laminated material workpiece (the CrC x N y The film layer is on the surface of the stainless steel material) as the anode, the graphite plate as the cathode, the workpiece and the graphite plate are placed in the above deplating solution, and the current density is 1A / dm 2 , electrolytic stripping was carried out at a temperature of 25° C. for 10 min, and the workpiece was taken out and cleaned.
[0058] Example 7 The composition of the deplating solution of the present embodiment is as follows: 8wt% potassium sodium tartrate, 6wt% sodium gluconate, 0.5wt% EDTA-2Na, 2wt% malic acid, 5wt% K2HPO4, 2wt% propylene glycol butyl ether, 76.5wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 6.2 and a conductivity of 63201μs / cm.
[0059] The electrolytic stripping process is as follows: CrC x N y Titanium alloy-aluminum alloy laminated material workpiece (the CrC x N y The film layer is on the surface of the titanium alloy material) as the anode, the graphite plate as the cathode, the workpiece and the graphite plate are placed in the above-mentioned deplating solution, and the current density is 1A / dm 2 , electrolytic stripping was carried out at a temperature of 25° C. for 10 min, and the workpiece was taken out and cleaned.
[0060] Example 8 The composition of the deplating solution of the present embodiment is as follows: 1wt% sodium aspartate, 0.5wt% sodium gluconate, 0.1wt% EDTA-2Na, 1wt% citric acid, 8wt% Na2HPO4, 4wt% NaH2PO4, 1wt% ethylene glycol butyl ether, 84.4wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 6.6 and a conductivity of 80836μs / cm.
[0061] The electrolytic stripping process is as follows: CrC x The stainless steel-aluminum alloy laminated material workpiece (the CrC x The film layer is on the surface of the stainless steel material) as the anode, the graphite plate as the cathode, the workpiece and the graphite plate are placed in the above deplating solution, and the current density is 2A / dm 2 , electrolytic stripping was carried out at a temperature of 25°C for 15 minutes, and the workpiece was taken out and cleaned.
[0062] Example 9 The composition of the deplating solution of the present embodiment is as follows: 1wt% sodium aspartate, 0.5wt% sodium gluconate, 0.1wt% EDTA-2Na, 1wt% citric acid, 8wt% Na2HPO4, 4wt% NaH2PO4, 1wt% ethylene glycol butyl ether, 84.4wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 6.6 and a conductivity of 80836μs / cm.
[0063] The electrolytic stripping process is as follows: CrC x Titanium alloy-aluminum alloy laminated material workpiece (the CrC x The film layer is on the surface of the titanium alloy material) as the anode, the graphite plate as the cathode, the workpiece and the graphite plate are placed in the above-mentioned deplating solution, and the current density is 2A / dm 2 , electrolytic stripping was carried out at a temperature of 25° C. for 10 min, and the workpiece was taken out and cleaned.
[0064] Example 10 The composition of the deplating solution of the present embodiment is as follows: 5wt% potassium sodium tartrate, 1wt% sodium gluconate, 3wt% EDTA-2Na, 0.5wt% citric acid, 1wt% Na2HPO4, 0.5wt% polyvinyl pyrrolidone, 89wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 5.5 and a conductivity of 40654μs / cm.
[0065] The electrolytic stripping process is as follows: CrC x N y The stainless steel-aluminum alloy laminated material workpiece (the CrC x N y The film layer is on the surface of the stainless steel material) as the anode, the graphite plate as the cathode, the workpiece and the graphite plate are placed in the above deplating solution, and the current density is 2.5A / dm 2 , electrolytic stripping was carried out at a temperature of 25°C for 15 minutes, and the workpiece was taken out and cleaned.
[0066] Embodiment 11 The composition of the deplating solution of the present embodiment is as follows: 5wt% potassium sodium tartrate, 1wt% sodium gluconate, 3wt% EDTA-2Na, 0.5wt% citric acid, 1wt% Na2HPO4, 0.5wt% polyvinyl pyrrolidone, 89wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 5.5 and a conductivity of 40654μs / cm.
[0067] The electrolytic stripping process is as follows: CrC x N y Titanium alloy-aluminum alloy laminated material workpiece (the CrC x N y The film layer is on the surface of the titanium alloy material) as the anode, the graphite plate as the cathode, the workpiece and the graphite plate are placed in the above-mentioned deplating solution, and the current density is 2.5A / dm 2 , electrolytic stripping was carried out at a temperature of 25° C. for 10 min, and the workpiece was taken out and cleaned.
[0068] Comparative Example 1 The composition of the deplating solution of this comparative example is as follows: 3wt% sodium aspartate, 2wt% sodium gluconate, 1wt% citric acid, 1.2wt% Na2HPO4, 0.5wt% isomeric tridecanol polyoxyethylene ether, 92.3wt% deionized water. The above raw materials are stirred evenly to obtain a deplating solution with a pH of 3.6 and a conductivity of 13235μs / cm.
[0069] The electrolytic stripping process is as follows: The metal Cr and CrC x The stainless steel workpiece of the composite film layer is used as the anode and the graphite plate is used as the cathode. The workpiece and the graphite plate are placed in the above-mentioned deplating solution at a current density of 2A / dm 2 , electrolytic stripping was carried out at a temperature of 30°C for 15 minutes, and the workpiece was taken out and cleaned.
[0070] Comparative Example 2 The composition of the deplating solution of this comparative example is as follows: 10wt% sodium gluconate, 10wt% sodium potassium tartrate, 0.1wt% EDTA-2Na, 0.2wt% citric acid, 0.3wt% Na2HPO4, 1wt% ethylene glycol butyl ether, 78.4wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 5.0 and a conductivity of 35689μs / cm.
[0071] The electrolytic stripping process is as follows: The metal Cr and CrC x The stainless steel-aluminum alloy laminated material workpiece of the composite film layer is used as the anode (the metal Cr and CrC x The composite film layer is on the surface of the stainless steel material), the graphite plate is used as the cathode, and the workpiece and the graphite plate are placed in the above-mentioned deplating solution with a current density of 1A / dm 2 , electrolytic stripping was carried out at a temperature of 25°C for 15 minutes, and the workpiece was taken out and cleaned.
[0072] Comparative Example 3 The composition of the deplating solution of this comparative example is as follows: 0.5wt% sodium gluconate, 1wt% EDTA-2Na, 1wt% citric acid, 8wt% KH2PO4, 8wt% Na2HPO4, 1wt% polyethylene glycol, 80.5wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 7.5 and a conductivity of 89537μs / cm.
[0073] The electrolytic stripping process is as follows: The metal Cr and CrC x The stainless steel-aluminum alloy laminated material workpiece of the composite film layer is used as the anode (the metal Cr and CrC x The composite film layer is on the surface of the stainless steel material), the graphite plate is used as the cathode, and the workpiece and the graphite plate are placed in the above-mentioned deplating solution with a current density of 1A / dm 2 , electrolytic stripping was carried out at a temperature of 25°C for 15 minutes, and the workpiece was taken out and cleaned.
[0074] Comparative Example 4 The composition of the deplating solution of this comparative example is as follows: 1wt% tetrasodium iminodisuccinate, 1wt% EDTA-2Na, 5wt% triethanolamine, 1wt% polyvinylpyrrolidone, 92wt% deionized water. The above raw materials were stirred evenly to obtain a deplating solution with a pH of 9.7 and a conductivity of 6817μs / cm.
[0075] The electrolytic stripping process is as follows: The metal Cr and CrC x The stainless steel-aluminum alloy laminated material workpiece of the composite film layer is used as the anode (the metal Cr and CrC x The composite film layer is on the surface of the stainless steel material), the graphite plate is used as the cathode, and the workpiece and the graphite plate are placed in the above-mentioned deplating solution with a current density of 2.5A / dm 2 , electrolytic stripping is carried out at a temperature of 30°C for 30 minutes, and the workpiece is taken out and cleaned.
[0076] Performance Testing (1) Stripping effect test Visually inspect whether the surface of the substrate is smooth and flat after stripping, and whether there is corrosion such as discoloration and loss of gloss. The test results are shown in Table 1 and Figure 1-5 shown.
[0077] Table 1 Stripping effect Stripping effect Example 1 The surface of the workpiece substrate is smooth and flat, and the coating is completely removed Example 2 The surface of the workpiece substrate is smooth and flat, and the coating is completely removed Example 3 The surface of the workpiece substrate is smooth and flat, and the coating is completely removed Example 4 The surface coating of the stainless steel workpiece is completely removed, and the surface is smooth and flat; the surface of the aluminum alloy workpiece has no discoloration or weight loss, and maintains its original luster Example 5 The coating on the titanium alloy surface of the workpiece is completely removed, and the surface is smooth and flat; the aluminum alloy surface of the workpiece has no discoloration or weight loss, and maintains its original luster Example 6 The surface coating of the stainless steel workpiece is completely removed, and the surface is smooth and flat; the surface of the aluminum alloy workpiece has no discoloration or weight loss, and maintains its original luster Example 7 The coating on the titanium alloy surface of the workpiece is completely removed, and the surface is smooth and flat; the aluminum alloy surface of the workpiece has no discoloration or weight loss, and maintains its original luster Example 8 The surface coating of the stainless steel workpiece is completely removed, and the surface is smooth and flat; the surface of the aluminum alloy workpiece has no discoloration or weight loss, and maintains its original luster Example 9 The coating on the titanium alloy surface of the workpiece is completely removed, and the surface is smooth and flat; the aluminum alloy surface of the workpiece has no discoloration or weight loss, and maintains its original luster Example 10 The surface coating of the stainless steel workpiece is completely removed, and the surface is smooth and flat; the surface of the aluminum alloy workpiece has no discoloration or weight loss, and maintains its original luster Embodiment 11 The coating on the titanium alloy surface of the workpiece is completely removed, and the surface is smooth and flat; the aluminum alloy surface of the workpiece has no discoloration or weight loss, and maintains its original luster Comparative Example 1 There is still a small amount of coating remaining on the workpiece surface Comparative Example 2 There is still some coating left on the stainless steel surface of the workpiece; there is slight discoloration on the aluminum alloy surface of the workpiece Comparative Example 3 There is still some coating left on the stainless steel surface of the workpiece; there is slight discoloration on the aluminum alloy surface of the workpiece Comparative Example 4 There is still a lot of coating left on the stainless steel surface of the workpiece; there is discoloration on the aluminum alloy surface of the workpiece From Table 1 and Figure 1-5It can be seen that the deplating effect of the deplating solution of each embodiment of the present application on the workpiece is better than that of the comparative example, and the chromium-containing film layer is deplated cleanly without damaging the substrate. The deplating solution provided in the present application has a good deplating effect on a metal substrate with a chromium-containing film layer plated on at least part of the surface, and does not damage the metal substrate.
[0078] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A stripping solution for stripping a chromium-containing film, characterized in that: Based on the total mass of the deplating solution, the deplating solution includes 1-15wt% of an organic salt, 0.1-5wt% of a chelating agent, 1-15wt% of a pH buffer, 0.1-3wt% of a wetting agent and 60-95wt% of deionized water; wherein the organic salt is an organic acid sodium salt and / or an organic acid potassium salt.
2. The deplating solution according to claim 1, wherein The organic acid sodium salt includes one or more of sodium gluconate, sodium aspartate, potassium sodium tartrate, sodium tartrate, sodium citrate, sodium malate, disodium iminodisuccinate and tetrasodium iminodisuccinate; The organic acid potassium salt includes one or more of potassium gluconate, potassium tartrate, potassium citrate and potassium malate.
3. The deplating solution according to claim 1, wherein Based on the total weight of the deplating solution, the deplating solution consists of 1-15wt% of an organic salt, 0.1-5wt% of a chelating agent, 1-15wt% of a pH buffer, 0.1-3wt% of a wetting agent and 60-95wt% of deionized water.
4. The deplating solution according to claim 1, wherein Based on the total mass of the deplating solution, the deplating solution includes 5-10wt% of an organic salt, 0.1-2wt% of a chelating agent, 3-8wt% of a pH buffer, 0.5-2wt% of a wetting agent and 75-95wt% of deionized water.
5. The deplating solution according to claim 1, wherein The pH of the deplating solution is 4-7.
6. The deplating solution according to claim 5, wherein The pH of the deplating solution is 5.5-6.
5.
7. The deplating solution according to claim 1, wherein The conductivity of the deplating solution is 10000-100000 μs / cm.
8. The deplating solution according to claim 1, wherein The chelating agent includes one or more of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, hydroxyethylidene diphosphonic acid, disodium hydroxyethylidene diphosphonic acid and tetrasodium hydroxyethylidene diphosphonic acid.
9. The deplating solution according to claim 1, wherein The pH buffer comprises an organic acid and a phosphate; wherein the organic acid comprises one or more of aminoacetic acid, glycolic acid, citric acid, malic acid and tartaric acid; The phosphate includes one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate and dipotassium hydrogen phosphate.
10. The deplating solution according to claim 9, characterized in that The mass ratio of the organic acid to the phosphate is 1:(0.5-15).
11. The deplating solution according to claim 10, characterized in that The mass ratio of the organic acid to the phosphate is 1:(1-10).
12. The deplating solution according to claim 1, characterized in that The wetting agent is one or more of ethylene glycol butyl ether, diethylene glycol butyl ether, propylene glycol butyl ether, propylene glycol, glycerol, isopropyl alcohol, polyvinyl pyrrolidone and polyethylene glycol.
13. An electrolytic stripping method, characterized in that: The method comprises the following steps: using a metal substrate having at least a portion of its surface covered with a chromium-containing film layer as an anode, and placing the metal substrate together with a cathode material in a deplating solution for electrolytic deplating; the deplating solution is the deplating solution according to any one of claims 1 to 12.
14. The electrolytic stripping method according to claim 13, characterized in that: The temperature of the deplating solution is 10-45°C; the current density of the deplating solution is 0.5-5A / dm 2 ; The electrolytic stripping time is 5-30min.
15. The electrolytic stripping method according to claim 13, characterized in that: The chromium-containing film layer includes one or more of a metal chromium plating layer, chromium carbide, chromium nitride and chromium carbonitride.
16. The electrolytic stripping method according to claim 13, characterized in that: The metal substrate includes one of stainless steel, titanium alloy, stainless steel-aluminum alloy laminated material and titanium alloy-aluminum alloy laminated material.
17. The electrolytic stripping method according to claim 13, characterized in that: The cathode material includes one of stainless steel or graphite plate.